Epistle as Means of Religious Communication (Linguostylistic Studies, 2015)
The article presents the analysis of religious communication specificity, peculiarities of communicative act construction with the help of contemporary religious epistles. The main structural-semantic characteristics of this type of text are highlighted. The primary attention is drawn to the means of epistles’ representations, the role of the sender and the recipient of this text type. The differential features of verbal and written form of epistle transmission are defined. The factors which are supporting (or vice versa – inhibiting) the effectiveness of such means of religious communication are determined. Key words: religious epistle, communication, communicative act, addresser, addressee, sender. References